Cancer Chemoprevention: Classic and Epigenetic Mechanisms Inhibiting Tumorigenesis. What Have We Learned So Far? - Melo, Fabiana Henriques Machado de; Oliveira, Julia Salles; Sartorelli, Viviani Olivastro Bressani; Montor, Wagner Ricardo (Frontiers in Oncology, 2018)
Cancers derive from step by step processes which are differentiated by the progressively accumulated mutations. For some tumors there is a clear progressive advancement from benign lesions to malignancy and for these, preventive screening programs exist. In such cases having those benign lesions are a clear indicator of predisposition while for some other cases, familial patterns of cancer incidence and the identification of mutations are the main indicators of higher risk for having the disease. For patients identified as having predisposition, chemoprevention is a goal and in some cases a possibility. Chemoprevention is the use of any compound, either natural or synthetic that abrogates carcinogenesis or tumor progression, through different mechanisms, some of which have already been described. For example, the classic mechanisms may involve activation of free radical scavenging enzymes, control of chronic inflammation and downregulation of specific signaling pathways. More recently, epigenetics allowed further understanding of the chemopreventive potential of several agents, such as sulforaphane, green tea derived compounds, resveratrol, isoflavones and others which we exploit in this review article. Throughout the text we discuss the properties compounds should have in order to be classified as chemopreventive ones and the challenges in translational research in this area, as lots of the success achieved in vitro cannot be translated into the clinical settings, due to several different drawbacks, which include toxicity, cost, dose definition, patient adherence and regimen of use.